China's and India's challenge to Latin America : (World Bank, 2009)
The economic successes of China and India are viewed with admiration but also with concern because of the effects that the growth of these Asian economies may have on the Latin American and Caribbean (LAC) region. The evidence in "China's and India's Challenge to Latin America" indicates that certain manufacturing and service industries in some countries have been negatively affected by Chinese and Indian competition in third markets and that LAC imports from China and India have been associated with modest unemployment and adjustment costs in manufacturing industries. The book also provides substantial evidence of positive aggregate effects for LAC economies associated with China's and India's greater presence in world exports, financial flows, and innovation. Chinese and Indian growth is creating new production possibilities for LAC economies, particularly in sectors that rely on natural resources and scientific knowledge.